Samuel Hearne and the Inuit Oral Tradition - McGrath, Robin (Studies in Canadian Literature, 1993)
In Samuel Hearne’s A Journey From Prince of Wales Fort, the description of the massacre of the Inuit at Bloody Falls is a descent into the heart of darkness, a confrontation with everything that supposedly-civilized European man faced in the New World. Hearne, like other non-Native explorers, constructed the story with contrasting images of the violent, savage (male) Indian and the peaceful, sensuous (female) Eskimo/Inuit. Inuit storytellers also shaped their accounts to fit the expectations of their listeners. Copper Inuit storytellers identity two separate massacre stories: the Navarana story and another version with some similar elements. The two stories and their variants contain common elements: a fight between two disparate groups (not tribal infighting); some survivors; a specific location (which varies); a revenge motif or the threat of retaliation; the marriage between a Native woman and a stranger (either white or Indian); and the use of magic. The presence of European figures in many of the Coppermine Inuit massacre stories suggests that the massacre which Hearne claimed to have witnessed did happen at the Falls and his presence was noted by survivors.